#39 Design, synthesis and studies of novel imidazoles - Chandra, Priyanka; Ganguly, Swastika; Ghosh, Manik (Journal of Pharmaceutical Chemistry, 2022)
With reference to our previously reported work on imidazoles, herein our objectives are to report the molecular docking studies of the synthesized imidazole analogs 2(a-f) into the non-nucleoside inhibitory binding pocket (NNIBP) of HIV-1-reverse transcriptase (PDB ID: 1RT2). The methodology consisted of the drawing of the chemical structures in Chem Office version 15.0.0.106 and the docking of these compounds in the NNIBP of HIV-1- RT with the help of Autodock Vina software. Binding mode analysis of all the docked compounds was carried out in the non-nucleoside inhibitory binding pocket of HIV-1-reverse transcriptase (PDB ID: 1RT2). All the compounds except compound 2c showed different interactions with the NNIBP. H-bonding interactions were observed for compounds 2b, 2d, 2e & 2f, whereas pi-pi-interactions were obtained for compounds 2a & 2f. Predictive ADMET studies were carried out for all the compounds. All the compounds were found to have drug-like properties. Among all the compounds, compound 2a was found to have the highest dock score when compared to the standard Nevirapine, whereas the best interaction was obtained for compound 2f. It is hoped that compounds 2a (E)-2-(2-methyl-4 nitro-1H-imidazol-1-yl)-3-phenyl-1-(p-tolyl)prop-2en-1-one & 2f (E)-3-(3,4-dimethoxyphenyl)-2-(2-methyl-4-nitro-1H-imidazol-1 yl)-1-(p-tolyl)prop-2-en-1-one) may act as a moiety which could be explored further for the synthesis of newer analogs which could act as non-nucleoside reverse transcriptase inhibitors against HIV-1- RT.